2021
DOI: 10.1016/j.ejro.2021.100333
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial pulsatile dynamics of the thoracic aorta and impact of thoracic endovascular repair

Abstract: Altered motion of the thoracic aorta after thoracic endovascular aortic repair. • Geometric analysis with cardiac-gated computed tomography and computer modeling. • Decreased motion of the stented aorta and increased motion above the stented aorta. • Longitudinal curvature and diametric deformation affected by presence of endograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Recently, Suh et al 18 performed analysis on preoperative and postoperative ECG-gated CT scans of 11 regular, nonbranched Gore G-TAG and Cook TEVAR patients and investigated centerline parameters and diameters of the aorta as well. The maximal curvature, both phase-averaged (40-50 m −1 vs ca.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Suh et al 18 performed analysis on preoperative and postoperative ECG-gated CT scans of 11 regular, nonbranched Gore G-TAG and Cook TEVAR patients and investigated centerline parameters and diameters of the aorta as well. The maximal curvature, both phase-averaged (40-50 m −1 vs ca.…”
Section: Discussionmentioning
confidence: 99%
“…Since size measurements are insufficient, current clinical guidelines aim to prevent morphologic changes indicative of aneurysmal degeneration and inferior outcomes [2,8]. Multiple studies have identified aortic centerline tortuosity, mean centerline curvature, and cross-sectional eccentricity as risk factors for deleterious outcomes [9][10][11][12][13][14]. Others have applied statistical shape analysis (SSA), a mathematical approach to modeling shape variation in a population, to replicating clinical diagnoses, predicting surgical outcomes, and modeling rupture risk in aortic disease [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the systemic effects, local stiffening, or severe stent‐graft oversizing appear to weaken the aortic wall, and to be associated with aneurysm formation, retrograde and stent‐graft‐induced new dissection, or rupture 10–13 . Moved from such considerations, several studies have exploited 3D analysis of in vivo medical images before 14 and after TEVAR 15,16 in order to quantify how the implantation of TEVAR endografts modifies the conformation and compliance of the repaired aorta, changing the geometry and dynamic motion of the implant site as well as adjacent regions of the aorta 17 . Accordingly, the in vivo aortic flow measurements before and after TEVAR have been performed using 4D flow MRI to assess the hemodynamic impact of endovascular treatment 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Moved from such considerations, several studies have exploited 3D analysis of in vivo medical images before 14 and after TEVAR 15,16 in order to quantify how the implantation of TEVAR endografts modifies the conformation and compliance of the repaired aorta, changing the geometry and dynamic motion of the implant site as well as adjacent regions of the aorta. 17 Accordingly, the in vivo aortic flow measurements before and after TEVAR have been performed using 4D flow MRI to assess the hemodynamic impact of endovascular treatment. 18 Alongside the in vivo measurement, engineering tool has been proved as effective to provide useful clinical insight for medical treatments.…”
mentioning
confidence: 99%